The First Genomic Analysis of Visna/Maedi Virus Isolates in China - Wu, Jian-Yong; Mi, Xiao-Yun; Yang, Xue-Yun; Wei, Jie; Meng, Xiao-Xiao; Bolati, Hongduzi; Wei, Yu-Rong (Frontiers in Veterinary Science, 2022)
Visna/Maedi virus (VMV) is a neglected pathogen that damages sheep and goats' nervous and respiratory systems. The virus was discovered 80 years ago and has been endemic in China for nearly four decades; nevertheless, there is little information regarding Chinese isolates' genotypes and genomic characteristics. In this study, the proviral DNA of strains isolated in 1985 and 1994 were extracted, and the proviral DNA was subjected to Illumina sequencing combined with Sanger sequencing of poor coverage regions. The results showed that the two isolates were clustered with genotype A2 and shared 78.3%–89.1% similarity to reference VMV genome sequences, with the highest similarity (88.7%–89.1%) to the USA strain USMARC-200212120-r (accession no. MT993908.1) and lowest similarity (78.3%–78.5%) to the Italian strain SRLV009 (accession no. MG554409.1). A maximum-likelihood tree showed that the Chinese VMV strains and the USA strain 1150 (accession no. MH916859.1) comprise a monophyletic group with a short tree branch. Our data filled the gap in genomic analysis and viral evolution in Chinese VMV strains, and would be benefit China’s source-tracing and eradication program development in China.